Penerapan Model Pembelajaran Kooperatif Tipe Tps Terhadap Kemampuan Pemecahan Masalah Matematis Siswa - Hanifah, Hanifah (Pendidikan Matematika Universitas PGRI Yogyakarta, 2019)
AbstractTeachers were required to create an active learning environment that could grow the students’ learning spirit and mathematical thinking. The cooperative learning model type TPS could provide opportunities for students to be more active and creative in solving mathematical problems. This research was a quasi-experimental study (t-test) with the nonequivalent control group design. The research was conducted to find out: (1) that students’ mathematical problem solving abilities that obtained cooperative learning type TPS were better than students who obtained direct instruction, (2) that students' mathematical problem solving abilities obtained the cooperative learning model type TPS achieve the KKM. The research population were all seventh grade students of SMP Negeri 1 Tulis. Sampling was done by cluster random sampling technique. The method of data collection in this research was a test of mathematical problem solving abilities. The data of the research results were processed using prerequisite tests, average difference test and completeness test. The results showed that: (1) students’ mathematical problem solving abilities that obtained cooperative learning type TPS were better than students who obtained direct instruction, (2) the value of students with the value of problem solving skills 70 that obtained the cooperative learning type TPS more than 75%. Keywords: Implementation, TPS, Mathematical Problem Solving Ability.AbstractTeachers were required to create an active learning environment that could grow the students’ learning spirit and mathematical thinking. The cooperative learning model type TPS could provide opportunities for students to be more active and creative in solving mathematical problems. This research was a quasi-experimental study (t-test) with the nonequivalent control group design. The research was conducted to find out: (1) that students’ mathematical problem solving abilities that obtained cooperative learning type TPS were better than students who obtained direct instruction, (2) that students' mathematical problem solving abilities obtained the cooperative learning model type TPS achieve the KKM. The research population were all seventh grade students of SMP Negeri 1 Tulis. Sampling was done by cluster random sampling technique. The method of data collection in this research was a test of mathematical problem solving abilities. The data of the research results were processed using prerequisite tests, average difference test and completeness test. The results showed that: (1) students’ mathematical problem solving abilities that obtained cooperative learning type TPS were better than students who obtained direct instruction, (2) the value of students with the value of problem solving skills 70 that obtained the cooperative learning type TPS more than 75%. Keywords: Implementation, TPS, Mathematical Problem Solving Ability.